The CSR discourse of environmental non-government organizations (ENGOs) its impact on community environmental management projects and relationship between ENGOs and corporations - Amparo, J. S. (Compendium of Human Ecology Researches in the Philippines, 2003)
The paper sought to discuss how CSR discourse is constructed and changed at the interface of corporations and NGOs, the factors that contribute to its framing or reframing, and the effects on practices of actors involved particularly in environmental management projects at the community level. It focused on environmental NGOs and their role in shaping the corporations discourse because ENGOs have had a longer history of dealing with corporations and are generally perceived to have some clout. Their origins in grassroots development work also make it valid to hypothesize that the ENGOs' perceptions of the common good and what could count as CSR would not necessarily be congruent with those of the corporate world.